Micromachined fabry-perot optical filters - Bartek, M. (1998)
The design, fabrication and measured characteristics of micromachined Fabry- Perot (F-P) optical filters for the visible spectral range are presented. Silver films of 40-50 nm thickness, evaporated on a 300 nm thick low-stress silicon nitride membrane, are used as high-quality mirrors. Two parallel mirrors, with a square aperture of up to 2x2 mm2 and initial cavity gap of 1.2 µm, form a tunable Fabry- Perot optical filter. One of the mirrors is fixed the other is under tension on a movable Si frame, which is electrostatically deflected to control the mirror spacing and parallelism. Results are compared with non-tunable F-P filters that are composed of an Ag/SiN/Ag or Ag/SiO2/Al layer stack. The FWHM of 40 nm (tunable filter) and 16 nm (non-tunable filter) have been achieved.